Eksistensi Advokat Sebagai Profesi Terhormat (Officium Nobile) dalam Sistem Negara Hukum di Indonesia - Hafidzi, Anwar (Khazanah: Jurnal Studi Islam dan Humaniora, 2015)
As mentioned in 1945 Constitution of the Republic of Indonesia article 1(3), Indonesia is a country of law. Reformation era has changed law system in Indonesia and given a big opportunity for law enforcement, espe- cially for advocate profession other than judicial power. As we know, advo- cate profession has been regulated in Laws No. 18 Year 2003 about advocate. According to that provision, advocate is in position as law enforcement, free and Independent which is guaranteed by laws and regulations, so that the exist- ence has the logical consequence that the advocate is aofficium nobille and have the same or equal position with other law enforcement authorities whom au- thorities also been determined by the laws and regulations in Indonesia, such as judges, prosecutors, and police. Sometimes ago , there were problems in regu- lating professional advocate which had caused heated debate among legal ex- perts, legislators and legal practitioners. It is because a submission of a draft of Law to amend the provisions of Law No. 18 year 2003 about the advocate.Kata Kunci : Advokat, Profesi Terhormat (Officium Nobile), Sistem Negara Hukum Indonesia.